2014
DOI: 10.1128/ec.00129-14
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between NDR Kinase Pathways Coordinates Cytokinesis with Cell Separation in Schizosaccharomyces pombe

Abstract: NDR (nuclear Dbf-2-related) kinases constitute key regulatory nodes in signaling networks that control multiple biological processes such as growth, proliferation, mitotic exit, morphogenesis, and apoptosis. Two NDR pathways called the septation initiation network (SIN) and the morphogenesis Orb6 network (MOR) exist in the fission yeast Schizosaccharomyces pombe. The SIN promotes cytokinesis, and the MOR drives cell separation at the end of cytokinesis and polarized growth during interphase. We showed previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 29 publications
7
27
0
1
Order By: Relevance
“…Consistent with this idea, we found that sts5∆ cells are prone to rupture at the site of cell separation (Figure 8—figure supplement 4A,d and B) similarly to cells that express ectopically active Orb6 during mitosis (Gupta et al, 2013Gupta et al, 2014). …”
Section: Resultssupporting
confidence: 74%
“…Consistent with this idea, we found that sts5∆ cells are prone to rupture at the site of cell separation (Figure 8—figure supplement 4A,d and B) similarly to cells that express ectopically active Orb6 during mitosis (Gupta et al, 2013Gupta et al, 2014). …”
Section: Resultssupporting
confidence: 74%
“…The authors demonstrated that cells failing to inactivate the MOR early during septation prematurely degraded the septum leading to lethality. Similar to our results here, this phenotype was reversed by deletion of wall degrading enzymes (Gupta et al, 2014). While fission yeast lack a sequence homolog of Fir1, a functional ortholog may exist.…”
Section: How Broadly Conserved Is the Eco Pathway?supporting
confidence: 89%
“…Important for CAR assembly. Control of polarized growth Nak1p and Sog2p Gupta et al, 2014;Gupta et al, 2013;Ray et al, 2010 Proposed mutual inhibition between SIN and MOR prevents conflicts between polar growth and cytokinesis.…”
Section: Turning the Sin Offmentioning
confidence: 99%
“…Sid2p phosphorylates Nak1p, and mutation of the phosphorylation sites on Nak1p results in continued cell elongation during mitosis and lysis at the time of septation (Gupta et al, 2014;Gupta et al, 2013). Pmo25p localisation to the SPBs requires SIN activity (Kanai et al, 2005;Mendoza et al, 2005), and it has been suggested that SINdependent sequestration of Pmo25p and Nak1p at the SPB prevents MOR activation (Ray et al, 2010).…”
Section: Sin-mor Crosstalkmentioning
confidence: 99%